1 Peter, 2 Peter, Jude : A Pentecostal Commentary - Skaggs, Rebecca, (Pentecostal Commentary Series, 2012)
This commentary, written from a distinctively Pentecostal perspective is primarily for pastors, lay persons and Bible students. It is based upon the best scholarship, written in popular language, and communicates the meaning of the text with minimal technical distractions. The author offers a running exposition on the text and extended comments on matters of special significance for Pentecostals. She acknowledges and interacts with alternative interpretations of individual passages, and her commentary also provides periodic opportunities for reflection upon and personal response to the biblical text.